GAME AS A METHOD OF DIAGNOSTICS AND EVALUATION OF SUBJECT RESULTS IN RUSSIAN AS A FOREIGN LANGUAGE LESSONS IN THE 5TH GRADE IN AN UZBEK SCHOOL (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the potential of game-based methods in the context of teaching Russian as a Foreign Language (RFL). The author examines the integration of game techniques into the educational process with the aim of enhancing learning effectiveness. The article presents specific examples of game tasks designed to develop various types of speech activity, including speaking, listening comprehension, and reading skills, as well as to expand students’ vocabulary. Special attention is given to adapting games to different language proficiency levels and learning objectives.